A geomorphological study of Auranga river basin, Jharkhand using geospatial techniques - Chandrakesh Maury,; Vishwambhar Nath Sharma, (National Geographical Journal of India, 2022)
The geomorphological setting defines a condition that influences landform development and morphological and structural characteristics of landforms. They are useful for land use planning, hazard mapping, and natural resource and environmental management. The present study is an investigation of the geomorphological characteristics of the Auranga river basin located in Jharkhand using a geospatial approach. The lineaments are extracted using ASTER DEM data and statistically analyzed to determine length, orientation, etc. Geomorphological units are identified and mapped using remote sensing data and GIS software. Slope and relief maps are prepared for a detailed understanding. It is observed that the maximum area of the basin is under the pediment pediplain complex (1075 sq. km) whereas the least expanded geomorphological unit is anthropogenic terrain (1.02 sq. km). The lineament analysis indicates major orientation and structural trends mainly in the NE-SW direction and zones of high lineament density are potential for groundwater prospecting in the basin. The result thus reveals the geomorphological setting of the Auranga river basin, hence proving the efficiency of the use of geospatial techniques for geomorphological studies.